2018
DOI: 10.1007/s12072-018-9892-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin level is associated with liver steatosis and fibrosis in Korean general population

Abstract: Elevation of serum ferritin level is significantly associated with NAFLD and blood ALT elevation in Korean general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 33 publications
5
36
1
1
Order By: Relevance
“…Our results corroborate that meat consumption, specifically red meat, was associated with ferritin concentration which could be influencing the development of NAFLD. Other research studies observed a relationship between ferritin and elevated ALT, a surrogate of liver damage [30,32,33]. In this context, we observed that participants above the median of red meat consumption presented higher ferritin and ALT concentrations than those with lower red meat consumption.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results corroborate that meat consumption, specifically red meat, was associated with ferritin concentration which could be influencing the development of NAFLD. Other research studies observed a relationship between ferritin and elevated ALT, a surrogate of liver damage [30,32,33]. In this context, we observed that participants above the median of red meat consumption presented higher ferritin and ALT concentrations than those with lower red meat consumption.…”
Section: Discussionsupporting
confidence: 66%
“…Excess circulating iron is potentially toxic, leading to the formation of reactive oxygen species, which can contribute to oxidative stress in NASH [28,29]. Increased serum ferritin level is closely related with insulin resistance and impaired glucose tolerance and NAFLD pathogenesis [30]. According to Willman et al, 2019, after a 6-month dietary intervention, a significant decrease on ferritin levels was found in participants corresponding to the “no red meat group” [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is the major site of systemic iron regulation [34]. Hepatocytes constitute the major parenchymal iron storage pool and contain large amounts of ferritin, the primary iron storage protein [35]. Iron is an essential but potentially toxic element that may promote the onset and progression of NAFLD by increasing oxidative stress and altering insulin signaling and lipid metabolism [14,15,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Hepatology International, Jung et al [21] examine the utility of serum ferritin to identify NAFLD using data from 25,597 participants in the Korean National Health and Nutritional Examination Survey (KNHANES). The population was divided by sex and then divided further into quartiles by ferritin levels.…”
mentioning
confidence: 99%